Case report: CD19-directed CAR-T cell therapy combined with BTK inhibitor and PD-1 antibody against secondary central nervous system lymphoma - Zhang, Wenqi; Huang, Chen; Liu, Ruixia; Zhang, Huichao; Li, Weijing; Yin, Shaoning; Wang, Lianjing; Liu, Wei; Liu, Lihong (Frontiers in Immunology, 2022)
Secondary central nervous system lymphoma (SCNSL) has grave prognosis and high mortality. Current therapeutic strategies for central nervous system (CNS) relapse of diffuse large B-cell lymphoma (DLBCL) were extremely limited. This report describes a young female patient with DLBCL and CNS relapse, who received low-dose CD19-CAR-T therapy followed by BTK inhibitor and PD-1 antibody after several lines of chemotherapy. There were limited reports on CAR-T therapy applied for SCNSL, particularly those in combination with targeted agents. The current treatment combination for this case provides a new regimen for CNS relapse from DLBCL.